Development of a complementary framework for implementing asset register solutions. Issue 6 (21st December 2021) - English, Lar; Yunusa‐Kaltungo, Akilu; Kidd, Moray; Labib, Ashraf
Abstract: A correctly compiled asset register within an asset information management system (AIMS) provides the foundation for a successful asset data solution. The lack of correctly structured asset registers within organizations is acknowledged among research and communities of practice. A case study identified anomalies that emerge when using established standards, after which a comprehensive solution for hierarchies, naming conventions and attributes was offered. While standards such as BS ISO 1007 and ISO 14224 provide overarching solution principles, such provisions are not all‐encompassing and exist across several sources, which makes the task of developing asset registers error‐prone and laborious. Challenges associated with software applications were highlighted through combining personal industrial experience as well as consultations with the existing body of knowledge. Recommendations that enable successful deployment of AIMS, with emphasis on its accommodation of a reliable asset register were then proffered. Scalability was addressed which enables an asset register to expand. This study describes a novel and simplified approach embodied within a single document. Combining the prescriptions of this article with existing literature will ease the delivery of an asset register. Abstract : The asset register is an important but under‐researched aspect of maintenance systems. This article addresses the gaps in the guidance offered in standards to develop an asset register and insert it to an asset information management system.